THE EFFECTIVENESS OF HUMAN ACTIVITY AND ITS INTELLECTUAL POTENTIAL AS A SOCIO-ECONOMIC INDICATOR - Taylyakova Feruza Sultanovna (Bright Mind Publishing, 2025)
In this article, it is stated that development in any society is a natural historical process connected with human activity and its intellectual potential, that the effectiveness of human activity depends on its intellectual potential, work skills and qualifications, internal and external motivation, that succession in the development of history and culture, as a special value, plays an important role in determining the criteria for the effectiveness of entrepreneurial activity, from the point of view of philosophers, the main social function of entrepreneurship consists in the introduction of certain new elements into the system of existing socio-economic contracts and agreements.
Keywords: Activity, content and essence, state leaders, effectiveness, human potential, classical philosophers, entrepreneurship, Jadids, human capital, metric problems.